CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF CHILDREN WITH HYMENOLEPIDOSIS IN BUKHARA - Khamidova Nargiza Kosimovna (World Scientific Research Journal, 2025)
SUMMARU: The data showed that the proportion of hymenolepiasis in different age groups of children about the same and vary from 19,0 ± 3,9 to 31,4 ± 7,8 %. In this rather alarming high rate among children aged less than 4 years (19,0 ± 3,9 %). Indicators symptomatic clinical form hymenolepiasis а^ had severe confinement and age ranged from 21,5 ± 5,1 to 30,8 ± 5,7 %, with subclinical form hymenolepiasis ranged from 12,3 ± 5,5 to 31,4 ± 7,8. Symptoms such as regular acute abdominal pain due to trauma of the mucous membrane of the intestinal wall hooks embedded parasite, subfebrile body temperature (usually marked increase to 37,5°, at least until 38,0°), moderately expressed normal and hypochromic anemia (marked reduction hemoglobin in the blood to 100 g / l or less), moderate enlargement of the liver pr., observed with high frequency in many children - up to 65,7 ± 8,1; 83,1 ± 4,7 %. In the manifest form, epileptiform convulsions, frequent diarrhea mixed with blood, dysbacteriosis are noted, which were recorded in most children - from 67.7 ± .8 to 87.7 ± 4.1% of cases. Complex antiallergic and antiparasitic treatment has a pronounced immunological effect, activates the severity of the immune response, switches the nature of the immune response to suppressor, and thereby contributes to a more rapid relief of the allergic process in the body.